SOCIAL IMPACT ANALYSIS OF MASS COMMUNICATION ON COMMUNITY IN THE SOCIETY 5.0 ERA - Siti Wuryan; Mustofa, Muhamad Bisri; Rezha Mardianty Rachmy; Sarah Nur Laila Indriyani; Septi Jelita Putri; Tri Yana Dea Sari (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2022)
The Society 5.0 era is considered a phenomenon of combining cyber technology with automation technology, which is characterized by changes in various sectors.  In this case, mass communication is system communication that is carried out through mass media and has a significant impact, especially in its application in everyday life with diverse impacts. This research uses qualitative methods while using a library research approach. The results of observations and literacy studies conducted by the author concluded that mass communication has a considerable social impact on society along with technological developments. Because the media plays a big role in the method of replacing existing social norms with new ones, even changing and creating new ones.